An anion exchange membrane, a method for preparing the same, and use thereof
Patent Information
- Application Number
- CN202311753301.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-19
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-12-19
AI Technical Summary
一般来说,提高IEC和SW可以提高电导率,但也会降低机械强度和耐碱稳定性;提高t-可以提高电导率,但也会增加制备难度和成本
[0024]1、相比于现存的阴离子交换膜结构,大多数为致密的无孔膜,因此离子电导率较低,实际使用能耗较高。本发明采用简单的筑孔方式及精细的分子结构设计,在传统的阴离子交换膜内部构筑大小均匀且可调控的纳米孔,极大提升了阴离子交换膜的离子电导率,且增强膜本身化学和机械稳定性,能够实现208mS/cm的氢氧根传导性能,显著优于现存美国、德国及日本进口的阴离子交换膜。
Smart Images

Figure CN117844038B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of anion exchange membrane technology, specifically to an anion exchange membrane, its preparation method, and its application. Background Technology
[0002] Anion exchange membranes are primarily composed of anion exchange resins, which are polyelectrolytes capable of conducting hydroxide anions and consist of a polymer backbone and cationic functional groups. Anion exchange membranes have a wide range of applications; they are crucial components in separation devices, purification devices, and electrochemical components, playing a vital role in the chlor-alkali industry, water treatment industry, heavy metal recovery, hydrometallurgy, and electrochemical industry. Among these, anion exchange membrane fuel cells and anion exchange membrane water electrolyzers are two important application areas of anion exchange membranes, which are of great significance to the field of sustainable hydrogen energy.
[0003] Ionic conductivity is one of the key factors affecting the performance of anion exchange membranes. It depends on the anion exchange capacity (IEC), water uptake (SW), and ion transport number (t). - Parameters such as IEC (Cat Functional Groups Per Gram of Dry Membrane) are used. IEC refers to the number of millimoles of cationic functional groups per gram of dry membrane, which determines the number of mobile OH groups in the membrane. - The quantity of OH- ions. SW refers to the number of grams of water absorbed per gram of dry membrane, which affects the diffusion rate of OH- ions in the membrane. t- refers to the proportion of OH- ions in the charge passing through the membrane, reflecting the degree of impurities from other ions in the membrane. Generally, increasing IEC and SW can improve conductivity but also reduce mechanical strength and alkali resistance; increasing t- can improve conductivity but also increases preparation difficulty and cost.
[0004] Therefore, there is a need to provide an anion exchange membrane with high ionic conductivity. Summary of the Invention
[0005] This application provides an anion exchange membrane, its preparation method, and its application. By constructing a nanoporous structure in the anion exchange membrane, the ionic conductivity of the anion exchange membrane is improved.
[0006] In a first aspect, this application provides a method for preparing anion exchange membranes, comprising the following steps:
[0007] S10: Disperse the water-soluble macrocyclic host molecule in water to obtain a first solution, wherein the water-soluble macrocyclic host molecule includes at least one of cucurbituril compounds, calixarene compounds, and cyclodextrin compounds;
[0008] S20: Disperse the anion exchange resin in a dipolar aprotic solvent to obtain a second solution;
[0009] S30: Mix the first solution and the second solution to make the water-soluble macrocyclic host molecule specifically bind to the cationic groups in the anion exchange resin to obtain a mixed slurry;
[0010] S40: The mixed slurry is coated and dried to form a film, the solvent in the mixed slurry is evaporated, and then the membrane material is washed to remove the water-soluble macrocyclic main molecules to obtain an anion exchange membrane.
[0011] According to this application, by utilizing the specific structure of the cationic groups in the anion exchange resin through the water-soluble macrocyclic host molecule, a nanoscale pore structure can be constructed during the formation of the anion exchange membrane. This increases the anion transport channels and reduces transmembrane resistance, thereby improving the ionic conductivity of the anion exchange membrane. Furthermore, this method is simple, suitable for industrial production applications, and does not introduce heteroatoms into the anion exchange resin, thus also improving the stability of the anion exchange membrane.
[0012] In some embodiments, the cucurbituril compounds include compounds of formula I, the calixarene compounds include compounds of formula II, and the cyclodextrin compounds include compounds of formula III.
[0013]
[0014] Among them, R1, R2, R3, R4, R5, R6, and R7 independently include -H, C1 to C4 alkyl groups, -NH2, -NHCH3, -OCH3, -OCH2CH3, -OCH2CH2CH3, -OCH2CH2CH2CH3, -OH, -SO3H, At least one of them; n1, n2, n3 independently represent 5, 6, 7, 8, 10.
[0015] In some embodiments, R1, R2, R3, R4, R5, R6, and R7 independently include at least one of -NH2, -NHCH3, -OCH3, -OCH2CH3, -OCH2CH2CH3, -OCH2CH2CH2CH3, -OH, and -SO3H.
[0016] In some implementations, n1, n2, and n3 independently represent 5 or 7.
[0017] In some embodiments, the water-soluble macrocyclic host molecule includes cucurbitacin compounds.
[0018] In some embodiments, the anion exchange resin includes at least one of aromatic anion exchange resin and aliphatic anion exchange resin; and / or the cationic group in the anion exchange resin includes at least one of alkyl quaternary ammonium salt, aryl quaternary ammonium salt, quaternary phosphorus salt, and organometallic salt.
[0019] In some embodiments, the ion exchange capacity of the anion exchange resin is 1 to 3 mmol / g.
[0020] In some embodiments, in step S30, the molar ratio of the water-soluble macrocyclic host molecule in the mixed slurry to the cationic group in the anion exchange resin is 1:1 to 10.
[0021] Secondly, this application provides an anion exchange membrane prepared according to the method described in any embodiment of the first aspect.
[0022] Thirdly, this application provides an electrochemical device, including an anion exchange membrane prepared according to the method described in any embodiment of the first aspect or an anion exchange membrane described in any embodiment of the second aspect.
[0023] The beneficial effects of this application are as follows:
[0024] 1. Compared to existing anion exchange membrane structures, most of which are dense, non-porous membranes, resulting in low ionic conductivity and high energy consumption in practical applications, this invention employs a simple pore-building method and a refined molecular structure design to construct uniformly sized and tunable nanopores within traditional anion exchange membranes. This significantly improves the ionic conductivity of the anion exchange membrane and enhances its chemical and mechanical stability, achieving a hydroxide ion conduction performance of 208 mS / cm, which is significantly superior to existing anion exchange membranes imported from the United States, Germany, and Japan.
[0025] 2. This application achieves the full-channel construction process through supramolecular recognition interactions. Compared with traditional channel formation methods, such as self-polymerizing microporous polymers or covalent organic framework materials, it does not require a complex synthesis process and has a series of advantages such as processability, good film-forming properties, and tensile strength. It can also avoid the problem of introducing heteroatoms into the main chain and can also provide guarantees in terms of chemical stability, enabling it to operate stably for about 1600 hours in an electrolysis water device. This makes it more feasible for subsequent applications in practical electrochemical devices.
[0026] 3. The anion exchange membrane of this invention enables precise control of its pore structure. Its key feature lies in utilizing the steric hindrance of macrocyclic molecules to precisely construct the pores of the linear polymer membrane material, thus forming uniform and dimensionally stable ion transport channels. Since the pore size is determined by the size of the macrocyclic molecules, accurate control can be achieved at the sub-nanometer or sub-2-nanometer level. Furthermore, based on the universality of supramolecular interactions, the proposed method has good versatility and can be widely applied to anion exchange resins with different main chains and different cation groups to complete pore construction.
[0027] 4. The supramolecular-induced nanoporous anion exchange membrane preparation method described in this invention is simple, does not require complex instrumentation, is easily scaled up industrially, and significantly improves process environmental conditions. This "supramolecular-induced nanoporous anion exchange membrane" can be used in traditional bipolar membrane electrodialysis as well as in novel energy conversion processes, including bipolar membrane water electrolysis, bipolar membrane fuel cells, bipolar membrane carbon dioxide reduction, etc. Utilizing the high conductivity and long service life of the supramolecular-induced nanoporous anion exchange membrane of this invention, the performance and lifespan of corresponding electrochemical reactors can be effectively improved, laying the foundation for the development of methods for constructing internal pores in anion exchange membranes and further industrialization. Attached Figure Description
[0028] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.
[0029] Figure 1 This is a schematic diagram of the supramolecular self-assembly of a water-soluble macrocyclic host molecule and anion exchange resin in one embodiment of this application.
[0030] Figure 2 This is a physical image of the anion exchange membrane in Example 1 of this application.
[0031] Figure 3 This is a scanning electron microscope image of the cross-section along the thickness direction of the anion exchange membrane in Example 1 of this application.
[0032] Figure 4 This is the carbon dioxide adsorption curve of the anion exchange membrane in Example 1 of this application.
[0033] Figure 5 The figure shows the hydroxide conductivity of the anion exchange membrane in Example 1 of this application at different temperatures.
[0034] Figure 6 The current density polarization curve is shown for the water electrolysis hydrogen production device including the anion exchange membrane in Embodiment 1 of this application.
[0035] Figure labels: 1. Anion exchange resin; 11. Cationic group; 2. Water-soluble macrocyclic host molecule.
[0036] The accompanying drawings illustrate specific embodiments of this application, which will be described in more detail below. These drawings and descriptions are not intended to limit the scope of the concept in any way, but rather to illustrate the concept of this application to those skilled in the art through reference to particular embodiments. Detailed Implementation
[0037] The various embodiments or implementation schemes in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments.
[0038] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with an embodiment or example is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0039] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this application, "multiple" means at least two, such as two, three, etc., unless otherwise explicitly specified.
[0040] As mentioned in the background section above, ionic conductivity is one of the key factors affecting the performance of anion exchange membranes, and it is necessary to improve the ionic conductivity of anion exchange membranes to improve their performance.
[0041] In related technologies, constructing porous structures within anion exchange membranes can increase the water content and ion channels, thereby improving anion migration rates and reducing transmembrane resistance. However, the nanopore preparation methods in these technologies mainly include template methods, phase separation methods, and electrospinning methods. These methods all have drawbacks; for example, template methods require the removal of template materials, phase separation methods require precise control of solvent parameters, and electrospinning methods require complex equipment and processes. Furthermore, the nanopore structures prepared by these methods are often inhomogeneous, unstable, or uncontrollable, leading to unstable or unsatisfactory performance of the anion exchange membrane.
[0042] Based on this, this application provides an anion exchange membrane, its preparation method, and its application. By co-mixing a water-soluble macrocyclic host molecule that can specifically bind to cation groups into anion exchange resin slurry, the membrane is formed through supramolecular self-assembly, resulting in a uniform, stable, and tunable nanoporous structure, thereby effectively improving its ionic conductivity. The specific embodiments of this application are described in detail below.
[0043] In a first aspect, this application provides a method for preparing anion exchange membranes, comprising the following steps:
[0044] S10: Disperse the water-soluble macrocyclic host molecule in water to obtain a first solution, wherein the water-soluble macrocyclic host molecule includes at least one of cucurbituril compounds, calixarene compounds, and cyclodextrin compounds;
[0045] S20: Disperse the anion exchange resin in a dipolar aprotic solvent to obtain a second solution;
[0046] S30: Mix the first solution and the second solution to allow the water-soluble macrocyclic main molecules to specifically bind with the cationic groups in the anion exchange resin, thus obtaining a mixed slurry;
[0047] S40: The mixed slurry is coated and dried to form a film, the solvent in the mixed slurry evaporates, and then the membrane material is washed to remove the water-soluble macrocyclic main molecules to obtain an anion exchange membrane.
[0048] According to this application, by utilizing the specific structure of the cationic groups in the anion exchange resin through the water-soluble macrocyclic host molecule, a nanoscale pore structure can be constructed during the formation of the anion exchange membrane. This increases the anion transport channels and reduces transmembrane resistance, thereby improving the ionic conductivity of the anion exchange membrane. Furthermore, this method is simple, suitable for industrial production applications, and does not introduce heteroatoms into the anion exchange resin, thus also improving the stability of the anion exchange membrane.
[0049] Specifically, in step S10, the water-soluble macrocyclic host molecule is dispersed in water to obtain a first solution. The water-soluble macrocyclic host molecule may include at least one of urea compounds, calixarene compounds, and cyclodextrin compounds. The above-mentioned water-soluble macrocyclic host molecule can have a specific structure with the cationic groups in the anion exchange resin. Sufficient dispersion is conducive to the smooth progress of subsequent supramolecular self-assembly, thereby promoting the formation of a uniform and stable nanoporous structure.
[0050] In step S20, the anion exchange resin is dispersed in a dipolar aprotic solvent to obtain a second solution. Generally, anion exchange resin has good dispersibility in dipolar aprotic solvents. At the same time, the dipolar aprotic solvent is miscible with water, which is more conducive to the supramolecular self-assembly of the water-soluble macrocyclic host molecule and the anion exchange resin, thereby promoting the formation of a uniform and stable nanoporous structure.
[0051] In step S30, the first solution and the second solution are mixed to allow the water-soluble macrocyclic host molecule to specifically bind with the cationic groups in the anion exchange resin, thereby achieving supramolecular self-assembly of the water-soluble macrocyclic host molecule and the anion exchange resin. A schematic diagram of this binding is shown below. Figure 1 The cationic groups 11 on the anion exchange resin 1 can specifically bind to the water-soluble macrocyclic host molecule 2, thereby forming a supramolecular self-assembled structure. The cyclic structure of the water-soluble macrocyclic host molecule 2 in the supramolecular self-assembled structure is conducive to the formation of nanoporous structures.
[0052] In step S40, the solvent is removed by drying to form a film, and then the membrane material is washed to remove the water-soluble macrocyclic main molecules to obtain an anion exchange membrane. During this process, the supramolecular self-assembly structure forms a nano-sized pore structure in the anion exchange membrane. This pore structure can increase the transport channels of anions and reduce the transmembrane resistance of anions. Therefore, the anion exchange membrane obtained by this method has a high ionic conductivity.
[0053] As can be seen from the above steps, this method is simple and does not require special processes or equipment. It only involves solution blending to enable the water-soluble macrocyclic host molecules and anion exchange resin to undergo supramolecular self-assembly to form a special structure, thereby constructing a nanoscale pore structure in the anion exchange membrane. Since the conditions required for supramolecular self-assembly are mild and do not require high temperature or high pressure conditions, the production cost is low and it is suitable for industrial applications.
[0054] Meanwhile, since this method does not involve modification of the anion exchange resin, it does not introduce other heteroatoms or groups into the anion exchange resin, and does not affect the stability of the anion exchange resin. Therefore, the anion exchange membrane obtained by this method has both high ionic conductivity and good stability, which can improve the service life of the anion exchange membrane.
[0055] It should also be noted that the size of the pore structure in the anion exchange membrane is mainly related to the size of the water-soluble macrocyclic host molecules. Therefore, the size of the pore structure can be controlled by adjusting their type. At the same time, the supramolecular self-assembly structure formed by the water-soluble macrocyclic host molecules and the anion exchange resin is related to the type and ratio of the two. By changing the relevant parameters, different supramolecular self-assembly structures can be obtained, thus obtaining anion exchange membranes with different structures. Therefore, the anion exchange membranes obtained by this method have high designability to adapt to different application scenarios.
[0056] It is understood that the water-soluble macrocyclic host molecule may include, but is not limited to, the compounds mentioned above. Those skilled in the art may also choose other known water-soluble compounds with cyclic structures that can specifically bind to the cationic groups in anion exchange resins.
[0057] In some embodiments, cucurbituril compounds include compounds of formula I, calixarene compounds include compounds of formula II, and cyclodextrin compounds include compounds of formula III.
[0058]
[0059] Among them, R1, R2, R3, R4, R5, R6, and R7 independently include -H, C1 to C4 alkyl groups, -NH2, -NHCH3, -OCH3, -OCH2CH3, -OCH2CH2CH3, -OCH2CH2CH2CH3, -OH, -SO3H, At least one of them; n1, n2, n3 independently represent 5, 6, 7, 8, 10.
[0060] In some of the above embodiments, specific structural formulas of certain cucurbituril compounds, calixarene compounds, and cyclodextrin compounds are defined. It should be noted that in the above structural formulas, dashed arcs represent rings formed by chemical bonds connecting structural units, and n1, n2, and n3 represent the number of structural units in the respective compounds. Compounds with the above structural formulas have a strong binding ability to cationic groups in anion exchange resins, which is beneficial to the formation of supramolecular self-assembly structures, thereby promoting the formation of porous structures in the anion exchange membrane and improving the ionic conductivity of the anion exchange membrane.
[0061] In some implementations, the R1 and R2, and R6 and R7 bonds form a ring. As an example, R1 and R2, and R6 and R7 can be bonded together... Bonding to form rings.
[0062] It should also be noted that R1, R2, R3, R4, R5, R6, and R7 are not limited to the above-mentioned groups. Those skilled in the art may also choose other known hydrophilic or hydrophobic groups that do not affect the binding with cationic groups in anion exchange resins.
[0063] As an example, a compound of formula I can be specifically described as follows:
[0064] At least one of them.
[0065] The compounds of formula II can be specifically as follows: At least one of them.
[0066] Compounds of formula III can be specifically described as follows: At least one of them.
[0067] In some embodiments, cucurbituril compounds may also include This compound is a derivative of cucurbituril. It has a good specific binding ability with the cationic groups in anion exchange resins and can also serve as a water-soluble macrocyclic host molecule to form a supramolecular self-assembled structure and construct a porous structure in anion exchange membranes.
[0068] In some embodiments, R1, R2, R3, R4, R5, R6, and R7 independently include at least one of -NH2, -NHCH3, -OCH3, -OCH2CH3, -OCH2CH2CH3, -OCH2CH2CH2CH3, -OH, and -SO3H.
[0069] In some of the above embodiments, R1, R2, R3, R4, R5, R6, and R7 may include substituent groups. These substituent groups have good hydrophilicity, which can further improve the hydrophilicity of the water-soluble macrocyclic host molecule, increase its solubility in water, and thus enable it to better perform supramolecular self-assembly with the anion exchange resin to form a more uniform and stable pore structure, thereby further improving the ionic conductivity of the anion exchange membrane.
[0070] In some implementations, n1, n2, and n3 independently represent 5 or 7.
[0071] In some of the above embodiments, the values of n1, n2, and n3 are further defined. When the number of structural units of the water-soluble macrocyclic host molecule is odd, its polarity is greater than when it is even. As a result, it has better dispersibility in water and is more likely to specifically bind with cations in the anion exchange resin, thereby forming a more uniform and stable pore structure and further improving the ionic conductivity of the anion exchange membrane.
[0072] In some embodiments, the water-soluble macrocyclic host molecule includes cucurbituril compounds.
[0073] In some of the above embodiments, cucurbituril compounds are more likely to specifically bind to cations in anion exchange resins compared to other water-soluble macrocyclic main molecules. Cucurbituril compounds also have better water solubility, resulting in better adjustability of the pore structure in the anion exchange membrane, making it easier to form a uniform and stable pore structure, and thus the anion exchange membrane has higher ionic conductivity.
[0074] In some embodiments, the anion exchange resin includes at least one of aromatic anion exchange resin and aliphatic anion exchange resin.
[0075] It should be noted that aromatic anion exchange resins and aliphatic anion exchange resins are distinguished based on whether the main chain structure of the anion exchange resin includes aromatic groups. An anion exchange resin whose main chain structure includes aromatic groups is an aromatic anion exchange resin, and vice versa, it is an aliphatic anion exchange resin.
[0076] The main chain structure of anion exchange resin has little impact on the supramolecular self-assembly process and the pore structure of the anion exchange membrane, and does not significantly affect the ionic conductivity. Therefore, the anion exchange resin can be either aromatic or aliphatic. The anion exchange resin mainly affects the mechanical strength and stability of the anion exchange membrane. Since aromatic anion exchange resins have better mechanical strength and stability, they are preferably included.
[0077] In some embodiments, the cationic groups in the anion exchange resin include at least one of alkyl quaternary ammonium salts, aryl quaternary ammonium salts, quaternary phosphorus salts, and organometallic salts.
[0078] In some of the above embodiments, the aforementioned cationic groups exhibit good binding ability with the water-soluble macrocyclic host molecules, which is beneficial for the formation of supramolecular self-assembly structures, thereby forming a more stable and uniform pore structure and improving the ionic conductivity of the anion exchange membrane. It is understood that the cationic groups in the anion exchange resin are not limited to the types mentioned above, and those skilled in the art can select other known cationic groups that can be grafted onto the anion exchange resin.
[0079] In some embodiments, the cationic groups in the anion exchange resin include alkyl quaternary ammonium salts. Alkyl quaternary ammonium salts exhibit better stability under high-temperature alkaline conditions, thus further improving the stability and lifespan of the anion exchange membrane. For example, the alkyl quaternary ammonium salt may be a quaternary ammonium salt having a piperidine structure or a spirocyclic structure.
[0080] As an example, the anion exchange resin may be at least one of poly(terphenyl-piperidinone) anion exchange resin, polyethylene anion exchange resin, and polyphenylene ether anion exchange resin.
[0081] In some embodiments, the ion exchange capacity of the anion exchange resin is 1 to 3 mmol / g.
[0082] In some of the above embodiments, the ion exchange capacity of the anion exchange resin is mainly related to the content of cationic groups in the cation exchange resin. The higher the ion exchange capacity, the better it is to improve the ionic conductivity of the anion exchange membrane, but it will also affect the stability of the anion exchange membrane. Therefore, the ion exchange capacity of the anion exchange resin can be 1 to 3 mmol / g, which can better balance the stability and ionic conductivity of the anion exchange membrane.
[0083] It should be noted that the ion exchange capacity of anion exchange resin has a meaning known in the art and can be determined using methods and instruments known in the art. For example, it can be determined by titration. Specifically, 0.3g of anion exchange resin is soaked in a saturated sodium chloride solution (80°C) overnight. Potassium chromate is used as an indicator, and silver nitrate standard solution is used to titrate the anion exchange resin. The titration endpoint is reached when a brick-red precipitate appears. The volume of silver nitrate standard solution consumed at this point is recorded. The IEC formula for calculating the ion exchange capacity of the anion exchange resin is:
[0084]
[0085] in, V represents the concentration of the silver nitrate standard solution. 消耗 The volume of silver nitrate standard solution consumed is expressed in m. 膜材料 This indicates the quality of the anion exchange membrane.
[0086] In some embodiments, the dipolar aprotic solvent includes, but is not limited to, dimethyl sulfoxide and N-methylpyrrolidone. Those skilled in the art may select other known dipolar aprotic solvents that can disperse anion exchange resins and are miscible with water, as needed.
[0087] In some embodiments, in step S30, the molar ratio of the water-soluble macrocyclic host molecule in the mixed slurry to the cationic group in the anion exchange resin is 1:1 to 10.
[0088] In some of the above embodiments, the molar ratio of the water-soluble macrocyclic host molecules to the cationic groups in the anion exchange resin in the mixed slurry is further defined. It is understood that this molar ratio affects the formation and stability of the supramolecular self-assembled structure, thereby affecting the morphology and size of the pore structure in the anion exchange membrane. Generally, the fewer the water-soluble macrocyclic host molecules and the more anion exchange resin, the greater the stability and mechanical strength of the pore structure, but the lower the ionic conductivity and water uptake. Conversely, increasing the content of the water-soluble macrocyclic host molecules can increase ionic conductivity and water uptake, but also decrease the stability and mechanical strength of the pore structure. The molar ratio of the water-soluble macrocyclic host molecules to the cationic groups in the anion exchange resin in the mixed slurry is 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, or any of the above values. Preferably, the molar ratio of the water-soluble macrocyclic host molecule to the cationic group in the anion exchange resin in the mixed slurry can be 1:3 to 10, at which point the anion exchange membrane performs better.
[0089] In some embodiments, in steps S10 and S20, the mass percentage of the water-soluble macrocyclic host molecule in the first solution and the mass percentage of the anion exchange resin in the second solution can be selected according to the solubility of the water-soluble macrocyclic host molecule in water and actual needs.
[0090] In some implementations, the dispersion or mixing process in steps S10, S20, and S30 can be assisted by mechanical stirring or ultrasound to obtain a more uniformly dispersed mixed system and promote the supramolecular self-assembly process.
[0091] In some embodiments, the dispersion or mixing process in steps S10, S20, and S30 can be carried out at 20–100°C. Appropriately increasing the temperature can promote the dispersion of the solute and at the same time promote the supramolecular self-assembly process; in addition, the temperature should not be too high to reduce solvent evaporation.
[0092] In some embodiments, the drying conditions in step S40 are 80–100°C.
[0093] In some embodiments, the washing process specifically includes washing the membrane material first with an alkaline solution and then washing with water to obtain an anion exchange membrane.
[0094] As an example, the alkaline solution can be a 2 mol / L potassium hydroxide aqueous solution.
[0095] Secondly, this application provides an anion exchange membrane prepared according to any embodiment of the first aspect.
[0096] According to this application, the anion exchange membrane is prepared according to any embodiment of the first aspect, and therefore has the beneficial effects of the first aspect.
[0097] Thirdly, this application provides an electrochemical device, including an anion exchange membrane prepared according to any embodiment of the first aspect or an anion exchange membrane according to any embodiment of the second aspect.
[0098] According to this application, the electrochemical device includes an anion exchange membrane prepared according to any embodiment of the first aspect or an anion exchange membrane according to any embodiment of the second aspect, and thus has the beneficial effects of the first aspect or the second aspect.
[0099] In some embodiments, the electrochemical device may be at least one of a fuel cell, a water electrolysis hydrogen production device, a carbon dioxide electroreduction device, and an electrocatalytic nitrogen reduction ammonia synthesis device. It is understood that the electrochemical device includes, but is not limited to, the above-mentioned types, and may also be other devices known to those skilled in the art that convert chemical energy into electrical energy or electrical energy into chemical energy.
[0100] As an example, anion exchange membranes can be used as isolation membranes in water electrolysis hydrogen production devices. These devices can also include cathodes and anodes, and those skilled in the art can select materials known to be suitable as cathodes and anodes for water electrolysis hydrogen production devices according to actual needs.
[0101] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0102] Ionic conductivity test: Ionic conductivity was determined using the four-electrode method at a temperature of 80℃. The resistance value in the parallel direction was measured, and the corresponding ionic conductivity was calculated.
[0103] Electrolysis of water test: The electrolyte was 6M KOH solution, the temperature was 80℃, the cathode catalytic electrode was NiMo alloy, the anode catalytic electrode was NiFe hydroxide, and the effective area was 1 cm². 2 The electrolysis current density corresponding to 1.8V was measured.
[0104] Example 1
[0105] 1) Add 0.02 g of unsubstituted cucurbita[7] (such as the compound of formula I, n1 is 7, and R1 and R2 of each structural unit are -H) of the water-soluble macrocyclic main molecule to 10 mL of deionized water and dissolve the solid in an ultrasonic dispersion device at room temperature.
[0106] 2) Prepare poly(terphenyl-piperidinone) anion exchange resin (iodine type, ion exchange capacity, i.e., the content of cationic groups, is 2.2 mmol / g). Dissolve 0.04 g of poly(terphenyl-piperidinone) anion exchange resin in 10 mL of dimethyl sulfoxide solution and stir thoroughly at 80 °C until completely dissolved.
[0107] 3) The homogeneous solution obtained in 1) and 2) is slowly added dropwise to a stirred glass bottle and mixed thoroughly, so that the water-soluble macrocyclic host molecule specifically binds to the cationic group of the anion exchange resin in the solution phase, and a solution with Tyndall effect is obtained, wherein the molar ratio of water-soluble macrocyclic host molecule to cationic group of anion exchange resin is 1:3.
[0108] 4) Spread the solution obtained in 3) evenly on a clean glass plate and place it in an oven at 80°C overnight to dry it, so as to achieve complete evaporation of the mixed solvent;
[0109] 5) Completely immerse the glass plate from step 4) in deionized water until a uniform and complete film detaches from the glass, then store the film in a humid environment.
[0110] 6) Immerse the membrane obtained in 5) in 2 mol / L KOH aqueous solution several times until the solution no longer shows obvious yellow color. During this process, ensure an inert gas atmosphere. Then, wash the membrane several times in deionized water until the solution is neutral to obtain an anion exchange membrane with supramolecular induced nanopores.
[0111] The anion exchange membrane obtained above was subjected to ionic conductivity and water electrolysis tests. The OH content of the anion exchange membrane at 80℃ was measured. - The ionic conductivity and the current density of water electrolysis at 1.8V at 80℃ are shown in Table 1.
[0112] Examples 2-12
[0113] The preparation method is roughly the same as in Example 1, except for the types of water-soluble macrocyclic host molecules and anion exchange resins, and the molar ratio of cationic groups in the water-soluble macrocyclic host molecules and anion exchange resins. Specific parameters are shown in Table 1.
[0114] The anion exchange membrane obtained above was subjected to ionic conductivity and water electrolysis tests. The OH content of the anion exchange membrane at 80℃ was measured. - The ionic conductivity and the current density of water electrolysis at 1.8V at 80℃ are shown in Table 1.
[0115] Comparative Example 1
[0116] The preparation method is roughly the same as in Example 1, except that no water-soluble macrocyclic host molecule is added.
[0117] The anion exchange membrane obtained above was subjected to ionic conductivity and water electrolysis tests. The OH content of the anion exchange membrane at 80℃ was measured. - The ionic conductivity and the current density of water electrolysis at 1.8V at 80℃ are shown in Table 1.
[0118] Table 1
[0119]
[0120]
[0121] As shown in Table 1, the ionic conductivity and water electrolysis current density of the anion exchange membranes obtained in each embodiment are significantly better than those in the comparative example. This indicates that the method provided in this application can effectively improve the ionic conductivity of the anion exchange membrane by constructing a porous structure on the anion exchange membrane through the self-assembly of water-soluble macrocyclic host molecules and anion exchange resin, thereby improving the hydrogen production efficiency of the water electrolysis device.
[0122] In addition, a physical image of the anion exchange membrane prepared in Example 1 is shown below. Figure 2 As shown, and its thickness-direction cross-section scanning electron microscope image as shown. Figure 3 This indicates that adding water-soluble macrocyclic main molecules during the preparation process does not affect the uniform film formation of the anion exchange resin.
[0123] Since the nanoscale pore structure in anion exchange membranes is not easily observed directly using an electron microscope, the anion exchange membrane prepared in Example 1 was used for carbon dioxide gas adsorption testing. Its carbon dioxide adsorption curve is shown below. Figure 4 This indicates that the anion exchange membrane has a high gas adsorption capacity, which shows that the specific surface area of the anion exchange membrane can be increased by using water-soluble macrocyclic host molecules, which indirectly proves the existence of the pore structure.
[0124] Example 1 shows the hydroxide conductivity of the anion exchange membrane prepared at different temperatures as follows: Figure 5 This indicates that the anion exchange membrane exhibits good ionic conductivity at different temperatures. The current density polarization curve of the water electrolysis hydrogen production device, including the anion exchange membrane in Example 1 of this application, is shown below. Figure 6 This indicates that when the anion exchange membrane is applied to a water electrolysis hydrogen production device, its high ionic conductivity can effectively increase the current density, thereby improving the hydrogen production efficiency.
[0125] To demonstrate the stability guarantee of the anion exchange membrane preparation strategy provided in this application, a long-term stability test was conducted under high current conditions for water electrolysis. The experiment showed that the anion exchange membrane prepared in Example 1 could achieve stable operation for up to 1600 hours, indicating that the anion exchange membrane has high stability. This is because no structures restricting the stability of heteroatoms in electrochemistry and high alkali concentrations were introduced during the construction of the nanopore structure. Therefore, this anion exchange membrane can simultaneously guarantee alkali resistance stability and has great potential for future practical applications.
[0126] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
Claims
1. A method for preparing anion exchange membranes, characterized in that, Includes the following steps: S10: Disperse the water-soluble macrocyclic host molecule in water to obtain a first solution, wherein the water-soluble macrocyclic host molecule includes at least one of cucurbituril compounds, calixarene compounds, and cyclodextrin compounds; S20: Disperse the anion exchange resin in a dipolar aprotic solvent to obtain a second solution; S30: Mix the first solution and the second solution to make the water-soluble macrocyclic host molecule specifically bind to the cationic groups in the anion exchange resin to obtain a mixed slurry; S40: The mixed slurry is coated and dried to form a film, the solvent in the mixed slurry is evaporated, and then the membrane material is washed to remove the water-soluble macrocyclic main molecules to obtain an anion exchange membrane. The cucurbituril compounds include compounds of formula I, the calixarane compounds include compounds of formula II, and the cyclodextrin compounds include compounds of formula III. Formula I, Formula II, Formula III, wherein R1, R2, R3, R4, R5, R6, and R7 in the water-soluble macrocyclic host molecule independently include -H, C1-C4 alkyl groups, -NH2, -NHCH3, -OCH3, -OCH2CH3, -OCH2CH2CH3, -OCH2CH2CH2CH3, -OH, -SO3H, , At least one of them, or; n1, n2, n3 independently represent 5, 6, 7, 8, 10; The anion exchange resin includes at least one of aromatic anion exchange resin and aliphatic anion exchange resin.
2. The method according to claim 1, characterized in that, R1, R2, R3, R4, R5, R6, and R7 independently include at least one of -NH2, -NHCH3, -OCH3, -OCH2CH3, -OCH2CH2CH3, -OCH2CH2CH2CH3, -OH, and -SO3H.
3. The method according to claim 1, characterized in that, n1, n2, and n3 independently represent 5 or 7.
4. The method according to any one of claims 1 to 3, characterized in that, The water-soluble macrocyclic host molecule includes cucurbitacin compounds.
5. The method according to claim 1, characterized in that, The cationic groups in the anion exchange resin include at least one of alkyl quaternary ammonium salts, aryl quaternary ammonium salts, quaternary phosphorus salts, and organometallic salts.
6. The method according to claim 1, characterized in that, The anion exchange resin has an ion exchange capacity of 1~3 mmol / g.
7. The method according to claim 1, characterized in that, In step S30, the molar ratio of the water-soluble macrocyclic host molecule in the mixed slurry to the cationic group in the anion exchange resin is 1:1~10.
8. An anion exchange membrane, characterized in that, Prepared by the method according to any one of claims 1 to 7.
9. An electrochemical device, characterized in that, This includes anion exchange membranes prepared by the method according to any one of claims 1 to 7 or anion exchange membranes according to claim 8.
Citation Information
Patent Citations
Cation exchange membrane based on cyclodextrin crosslinked polymer and preparation method and applications thereof
CN108929407A
Ionic conduction cross-linked substance, preparation method thereof, anion exchange membrane and application of anion exchange membrane
CN117106209A
